Keragaan Galur Padi Lahan Sawah Pasang Surut Type C Melalui Teknologi Ratun Kabupaten Rokan Hilir - Emi Sari Ritonga; Ida Nur Istina; Maizar Maizar (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2019)
Ritonga ES, Istina IN, Maizar M. 2019. The performance of the c type of swamp rice line through ratoon technology at Rokan Hilir Regency. Jurnal Lahan Suboptimal: Journal of Suboptimal Lands. 8(2):220-229. To support food security, the government set a national rice production target of 10 million tons in 2014. Its a trigger in agricultural innovation. The utilization of sub-optimal lands such as tidal lowland for the purpose of increasing food production and self-sufficiency and making swamps as a national food barn continue to be pursued, both through innovation and excavation and the development of local wisdom. Various technological innovations have been produced by the IAARD on tidal lowland, including increasing crop intensity (IP), genetic improvement in rice, and ratoon planting systems. The aim of this research was to get the type C tidal rice lines through ratoon technology. The research has been conducted at Pematang Sikek Village, Rimbo Melintang sub District, Rokan Hilir Regency with C type of tidal lowland using a Randomized Group Design with 4 replications. The rice strains tested included 11 tidal rice were with 11 types of tidal rice lines (G1, G3, G4, G6, G7, G8, G17, G20, G23, G45 , G53). The results showed that the best vegetative growth were G3 (118.33 cm), G7 (15.00 stems) Number of productive tillers was G4 (15.33 stems) while for generative growth G4 (2.50 t / ha), G53 ratoon (35.33 cm) 238.00 gram), weight of a thousand grains of G53 ratoon was (26.77 gram). G4 gives the highest production and adapted to Rokan Hilir tidal lowland.